Sistem Pendukung Keputusan Evaluasi Kinerja Karyawan dengan Metode SMART (Simple Multi Attribute Rating Technique) - Wawan Setiawan; Nurwahid Pranoto; Khoirul Huda (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Every company needs an employee performance appraisal system, for the evaluation of its employees in terms of quality and responsibility for their work. In evaluating the performance of employees at PT. MMC Group is still manually so it takes a long time and the impact on decision making time also takes a long time. Besides evaluation only on aspects of the strengths and weaknesses of employees, so the results of decisions taken are not accurate and subjective. Therefore we need a decision support system that can do calculations quickly, precisely and accurately based on predetermined criteria. The calculation method used in this study is the SMART (Simple Multi Attribute Rating Technique) method. There are 5 assessment criteria used, namely quality of work, integrity, loyalty, discipline and personality, while for alternative data as many as 10 employees are taken by cluster random sampling. To test the performance of the SMART method calculation results using the Confusion Metrix method. The results of this study are an accuracy rate of 90%, a precission of 100%, a recall of 88.88% and a specificity of 94.12%.